Exploring shared impact measurement : developing a framework for future action for the Zero Waste Network Aotearoa : a thesis prepared in partial fulfilment of the requirements for the degree of Master of Environmental Management at Massey University, New Zealand - Wray, Dorte (Massey University, 2020)
The Zero Waste Network (ZWN) represents community resource recovery enterprises (CREs) working to shift communities towards a circular economy via zero waste education, reuse and recycling activities in Aotearoa New Zealand. The CRE model produces a range of impacts, however there is currently no standardised approach to reporting these. This thesis aims to develop a framework of action towards the implementation of shared impact measurement within the ZWN. It was found that research participants understand and communicate CRE impact in a variety of ways. It is proposed that there are environmental, cultural, social and economic dimensions to CRE impact. These are explored and analytical and reporting tools are presented for each. Aiming to have practical application within the ZWN, this thesis uses an action research approach, involving ZWN members in its design and implementation. Interviews, a survey and focus groups were undertaken, allowing for a variety of qualitative and quantitative data to be collected. These were analysed using coding and basic statistical analysis methods.
Keywords: Impact; zero waste; community resource recovery; circular economy; action research; 410402 Environmental assessment and monitoring